2016
DOI: 10.1016/j.jprot.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic characterization of mucosal secretions in the eastern oyster, Crassostrea virginica

Abstract: The soft body surface of marine invertebrates is covered by a layer of mucus, a slippery gel secreted by mucocytes lining epithelia. The functions of this gel are diverse including locomotion, cleansing, food particles processing and defense against physicochemical injuries and infectious agents. In oysters, mucus covering pallial organs has been demonstrated to have a major importance in the processing of food particles and in the interactions with waterborne pathogens. Given the limited information available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 150 publications
(169 reference statements)
1
59
0
Order By: Relevance
“…Some bivalve lectin-encoding gene families are extremely expanded and comprise several hundred members, as suggested by proteomic [110] and transcriptome studies [20, 111, 112] and later confirmed on a whole genome scale in oyster [113]. The purplish Japanese mussel is no exception, as some important lectin-like gene families were also found among the most abundant ones in the de novo assembled transcriptome (Table 8).…”
Section: Resultsmentioning
confidence: 91%
“…Some bivalve lectin-encoding gene families are extremely expanded and comprise several hundred members, as suggested by proteomic [110] and transcriptome studies [20, 111, 112] and later confirmed on a whole genome scale in oyster [113]. The purplish Japanese mussel is no exception, as some important lectin-like gene families were also found among the most abundant ones in the de novo assembled transcriptome (Table 8).…”
Section: Resultsmentioning
confidence: 91%
“…This is supported by a growing body of evidence highlighting the role mucosal microbiomes in regulating host resistance to infection either directly [microbe-microbe interactions; 69, 119, 120] or indirectly via immune stimulation and maturation [44]. Our current understanding underlines the diversity of immune effectors at molluscan mucosal interfaces [65] and highlights the tailored immune response to pathogen stimuli [62]. This context raises fascinating questions around host-microbe crosstalk and feedback controls of these interactions and may lead to novel disease mitigation strategies and improve the assessment of resistant crops or the screening of probiotic candidates.…”
Section: Discussionmentioning
confidence: 88%
“…These act as a sieve, capturing food particles in the optimum range of 5-10 mm and moving them [ 2 0 _ T D $ D I F F ] towards the mouth [33]. In this process, mucus-and gill-associated microbiota may constitute a first defense against vibrios [42,43]. Thus, laboratory infection of animals where cultured bacteria are simply provided in a monoclonal state is unlikely to yield an accurate understanding of the factors that contribute to virulence.…”
Section: Experimental Ecology: Closing the Gap Between Natural And Lamentioning
confidence: 99%